Draft Fifth Five Year Plan (1974-1979) Mysore State - Planning Commission (Planning Commission, 1974)
Over 60 per cent of the State income comes from Agriculture as against the national share of 50 per cent. The contributions from secondary and tertiary sectors have been lower. The composition of the State income has not significantly changed in spite of latent potential which the State has for a faster development of the secondary and tertiary sectors. The average rate of growth from Agriculture and allied Sector for the period 1968-69 to 1971-72 works out to 6.5 per cent. On the other hand the tertiary sector viz., services sector registered a modest growth of 3 per cent per annum. In the process of development reduction in the share of primary sector in the State income where productivity is less and a gradual rise in share of secondary and tertiary sectors where productivity per employed person is expected to be more is a desirable goal to be attained. This transition is somewhat a slow process.
Mysore State